Social inequalities in early exit from employment in Germany: a causal mediation analysis on the role of work, health, and work ability - Max Rohrbacher; Hans Martin Hasselhorn (Nordic Association of Occupational Safety and Health (NOROSH), 2022)
OBJECTIVE: The aim of this study was to investigate the contribution of work factors, health, and work ability to social inequalities in early exit from employment among older employees in Germany. METHODS: Longitudinal data from the representative German lidA Cohort study was linked with employment register data to obtain maximum information on exit routes out of paid employment. Information of N=2438 respondents, aged 46 and 52 at baseline, were obtained for a follow-up of six years (2011-2017). Causal mediation analysis with inverse odds weighting was conducted using discrete-time survival outcomes and baseline measurements of the socioeconomic status (SES: education), work factors, health, and work ability. RESULTS: Older employees with low SES were at an increased risk of exiting employment early by receiving disability pension and through long-term unemployment but not through an unspecified labor market exit when compared to those with high and moderate SES. Low work ability accounted for up to 38% of the social inequalities in work exits into disability pension. Less-than-good physical health accounted for up to 59% of inequalities in work exits into long-term unemployment. Work factors contributed considerably to inequalities in exits through unemployment but not disability pension. CONCLUSIONS: This study finds social inequalities in early exits through disability pension and long-term unemployment among older employees in Germany, predominantly attributable to differences in work ability (disability pension) and physical health (unemployment). Investments in work ability and promotion of physical health may constitute promising approaches to counteract an increase of these inequalities.